Targeting and tailoring climate change communications. (18th June 2013) - Bostrom, Ann; Böhm, Gisela; O'Connor, Robert E.
Abstract : Social marketing studies suggest that targeting segments of the population, by assessing and addressing their values and motives for actions in the design of communications, can improve the effectiveness of health and environmental communications efforts. Guidance for climate change communication now routinely proposes targeting specific audience segments as a fundamental principle, despite ambiguity regarding what specific behaviors to target and a lack of empirical evidence for specific strategies. Audience segmentation strategies proposed to date for climate change communications resemble those used in other social marketing efforts, but can be proprietary or opaque, with little data on the effects of implementing them. Insufficient evidence exists to systematically demonstrate the effectiveness of targeting or tailoring climate change communications per se, other than by reference to related research on health and environmental risk communications. Meta‐analyses with systematic literature reviews, however, demonstrate that health risk communications can be more effective at changing attitudes and behaviors if they are tailored to the individual recipients' beliefs about their self‐efficacy. The advent of technology‐enabled microtargeting is rapidly expanding the opportunities for tailoring and targeting climate change communications and for adding to what we know from using them to make them effective. WIREs Clim Change 2013, 4:447–455. doi: 10.1002/wcc.234 This article is categorized under: Perceptions, Behavior, and Communication of Climate Change > Communication